2013
DOI: 10.1111/jsbm.12020
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Entrepreneurship Education on Human Capital at Upper-Secondary Level

Abstract: In this study we evaluate the impact of entrepreneurship education on human capital at the upper-secondary level using a quasi-experimental design. Data were collected from 494 students attending entrepreneurship education programs and from 238 in a control group. Our results indicate that some personality traits such as need for autonomy and risk propensity, as well as beliefs, can have a significant positive influence on entrepreneurial intention. Entrepreneurship education has a positive, albeit limited imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
130
1
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(147 citation statements)
references
References 64 publications
(91 reference statements)
7
130
1
9
Order By: Relevance
“…Based on this, a number of studies have found a positive effect of EE on EL outcomes such as understanding of key concepts of entrepreneurship (Volery et al 2013), abilities to discover new opportunities (DeTienne and Chandler 2004) and positive attitudes towards entrepreneurship (Peterman and Kennedy 2003;Walter and Dohse 2012). Martin, McNally, and Kay (2013) report extensive evidence about this relationship; the authors also commend future studies to address not only the effect of EE as such, but also of the degree of exposure to EE, on EL outcomes.…”
Section: The Effect Of Entrepreneurship Education At Universities On mentioning
confidence: 99%
See 2 more Smart Citations
“…Based on this, a number of studies have found a positive effect of EE on EL outcomes such as understanding of key concepts of entrepreneurship (Volery et al 2013), abilities to discover new opportunities (DeTienne and Chandler 2004) and positive attitudes towards entrepreneurship (Peterman and Kennedy 2003;Walter and Dohse 2012). Martin, McNally, and Kay (2013) report extensive evidence about this relationship; the authors also commend future studies to address not only the effect of EE as such, but also of the degree of exposure to EE, on EL outcomes.…”
Section: The Effect Of Entrepreneurship Education At Universities On mentioning
confidence: 99%
“…While the former refers to the 'experiences such as education and work experience that may or may not lead to knowledge and skills' , the latter are 'acquired knowledge and skills' (Unger et al 2011, 343). Analysing the results of EE through the lens of human capital theory implies exploring the outcomes of the human capital acquisition process and, in particular, to what extent the educational experiences (EE as investment in human capital) become entrepreneurial knowledge (EL outcomes or human capital assets) (Martin, McNally, and Kay 2013;Volery et al 2013). …”
Section: Conceptual Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…[Martin, McNally, Kay, 2013]. In particular, it contributes to formation of relevant beliefs and principles, as well as the ability to identify and exploit entrepreneurial opportunities and to enhance one's knowledge of entrepreneurship [Volery et al, 2013]. Stein Kristiansen and Nurul Indarti discovered that availability of information on venture creation ins and outs positively related to the development of entrepreneurial intentions [Kristiansen, Indarti, 2004].…”
Section: Theoretical Framework and Research Hypothesesmentioning
confidence: 99%
“…Based on the methods of other impact studies (e.g., Kolvereid and Moen, 1997;Wilson et al, 2007;Liao and Gartner, 2008;Olomi and Sinyamule, 2009;Kružić and Bulog, 2010), a structured sampling procedure with an adequate sample size for an ex ante/ex post design represents a further essential requirement for evaluating entrepreneurial narratives as an adequate teaching tool (Lorz et al 2013). In addition, because most EE studies are carried out at higher educational levels (e.g., Vanevenhoven and Liguori, 2013;Volery et al, 2013;Zhang et al, 2014), a focus on currently under-researched target groups such as students of vocational schools (Lorz et al, 2013) will enrich the academic discussion.…”
Section: Discussionmentioning
confidence: 99%